2013
DOI: 10.1002/jgra.50540
|View full text |Cite
|
Sign up to set email alerts
|

Protons and alpha particles in the expanding solar wind: Hybrid simulations

Abstract: [1] We present results of a two-dimensional hybrid expanding box simulation of a plasma system with three ion populations, beam and core protons, and alpha particles (and fluid electrons), drifting with respect to each other. The expansion with a strictly radial magnetic field leads to a decrease of the ion perpendicular to parallel temperature ratios as well as to an increase of the ratio between the ion relative velocities and the local Alfvén velocity creating a free energy for many different instabilities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…These instabilities act locally to increase T α⊥ and decrease T α according to both theory (e.g. Verscharen et al 2013;Matteini et al 2015;Seough & Nariyuki 2016), and expanding box simulations of an electron-proton-alpha solar wind (Hellinger et al 2003;Hellinger & Trávníček 2013). In addition to temperature anisotropy instabilities there are many other proposed mechanisms that could influence the observed non-adiabatic behaviour: alpha streaming instabilities (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…These instabilities act locally to increase T α⊥ and decrease T α according to both theory (e.g. Verscharen et al 2013;Matteini et al 2015;Seough & Nariyuki 2016), and expanding box simulations of an electron-proton-alpha solar wind (Hellinger et al 2003;Hellinger & Trávníček 2013). In addition to temperature anisotropy instabilities there are many other proposed mechanisms that could influence the observed non-adiabatic behaviour: alpha streaming instabilities (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…Both Ulysses (Goldstein et al, ; Matteini et al, ) and Helios observations (Marsch and Livi, ) indicate a differential streaming between the proton core and beam populations. Hellinger and Travnicek (, ) have indicated that solar wind expansion leads to an increasing ratio between the differential particle velocity and the local Alfvén speed, also leading to the oblique Alfvén wave instability.…”
Section: Source Of the Alfvén Wavesmentioning
confidence: 99%
“…Matteini et al (, ) and Hellinger and Travnicek () have mentioned the possibility of local Alfvén wave generation though an oblique fire hose instability caused by the expanding solar wind. Another source of free energy for this instability is associated the differential speed between the proton core and beam (or He ++ ) distributions (Hellinger & Travnicek, , ).…”
Section: Final Commentsmentioning
confidence: 99%
“…Similar ideas involving dissipative mechanisms related to interaction of Alfvén waves or KAWs and phase mixing have been examined in the context of the magnetospheric plasma sheet [ Lysak and Song , ] and in coronal loops [ Ofman and Aschwanden , ]. It has been shown that ion‐scale shear Alfvén waves can be excited by ion beams in the solar wind [ Hellinger and Trávníček , , ], and these can contribute to the formation of KAWs [ Nariyuki et al , ]. Many observations have shown that the proton distribution function in the solar wind can include a beam directed in the direction parallel to the local magnetic field [ Marsch , ; Marsch et al , ; Goodrich and Lazarus , ], with a drift speed of the order of the local Alfvén velocity [ Goldstein et al , ; Tu et al , ].…”
Section: Introductionmentioning
confidence: 98%